MODEL PENILAIAN SIKAP MORAL BERBASIS HIKAYAT TENGKORAK KERING DALAM PEMBELAJARAN PAI: STUDI DI MTS NURUL ISLAM KUANTAN SINGINGI - Fajar Illahi; Rina Rehayati Rehayati; Jamaluddin (SURAU : Journal of Islamic Education, 2026)
Moral attitude assessment in Islamic Religious Education (IRE) plays an important role in fostering students’ character development. However, its implementation in Islamic schools remains constrained by assessment models that have not effectively measured the authentic internalization of moral values. The research gap lies in the limited studies integrating Hikayat Tengkorak Kering as a basis for developing moral attitude assessment models in IRE. This study aims to analyze the implementation of a moral attitude assessment model based on Hikayat Tengkorak Kering at MTs Nurul Islam Kuantan Singingi. A qualitative approach with a case study design was employed. Data were collected through observations, interviews, and documentation and analyzed using data reduction, data display, and conclusion drawing techniques. The novelty of this study lies in the development of an assessment model that utilizes a religious tale as a medium for value internalization and a pedagogical assessment instrument. The findings indicate that the model is implemented authentically, continuously, and contextually, effectively strengthening the internalization of moral values, fostering students’ akhlakul karimah (noble character), and reinforcing character education in Islamic Religious Education.